Ubiquitin-mediated mechanisms of translational control. (December 2022) - Martínez-Férriz, Arantxa; Ferrando, Alejandro; Fathinajafabadi, Alihamze; Farràs, Rosa
Abstract: mRNAs translation to proteins constitutes an important step of cellular gene expression that is highly regulated in response to different extracellular stimuli and stress situations. The fine control of protein synthesis is carried out both qualitatively and quantitatively, depending on the cellular demand at each moment. Post-translational modifications, in turn regulated by intracellular signaling pathways, play a key role in translation regulation. Among them, ubiquitination, whose role is becoming increasingly important in the control of translation, determines a correct balance between protein synthesis and degradation. In this review we focus on the role of ubiquitination (both degradative K48-linkage type and non-degradative K63-linkage type and monoubiquitination) in eukaryotic translation, both at the pre-translational level during the biogenesis/degradation of the components of translational machinery as well as at the co-translational level under stressful conditions. We also discuss other ubiquitin-dependent regulatory mechanisms of mRNA protection and resumption of translation after stress removal, where the ubiquitination of ribosomal proteins and associated regulatory proteins play an important role in the global rhythm of translation.